Stochastic Dynamics Between HIV-1 Latent Infection and cART Efficacy Within the Brain Microenvironment (CSIAM Transactions on Life Sciences, 2025)
We develop a stochastic human immunodeficiency virus type 1 (HIV-1) infection model to analyze combination antiretroviral therapy (cART) dynamics in the brain microenvironment, explicitly accounting for two infected cell states: (1) productively infected and (2) latently infected populations. The model introduces two key epidemiological thresholds $- \ \overline{\mathcal{R}}_{c1} $ (productive infection) and $ \overline{\mathcal{R}}_{c2}$ (latent infection) $-$ and defines the stochastic control reproduction number as $ \overline{\mathcal{R}}_c = \max\{\overline{\mathcal{R}}_{c1}, \overline{\mathcal{R}}_{c2}\} $. Our analysis reveals three distinct dynamical regimes: (1) viral extinction $(\overline{\mathcal{R}}_c1):$ the system almost surely converges to a purely latent state, characterizing stable viral reservoir formation; (3) persistent productive infection $( \overline{\mathcal{R}}_c = \overline{\mathcal{R}}_{c1} > 1):$ the infection persists indefinitely with a unique stationary distribution, for which we derive the exact probability density function. And numerical simulations validate these theoretical predictions, demonstrating how environmental noise critically modulates HIV-1 dynamics in neural reservoirs. Our results quantify the stochastic balance between productive infection, latency establishment, and cART efficacy, offering mechanistic insights into viral persistence in the brain.
Keywords: Brain reservoirs; combination antiretroviral therapy; HIV-1 infection model; extinction; probability density function